Total tin (TSn) biomagnification: Evaluating organotin trophic flow and dispersion using hepatic TSn concentrations and stable isotope (C, N) data of nektonic organisms from Brazil. (October 2020) - Dorneles, Paulo R.; Schilithz, Priscila F.; Paiva, Thais de C.; Flach, Leonardo; Barbosa, Lupércio A.; Domit, Camila; Cremer, Marta J.; Azevedo-Silva, Claudio E.; Azevedo, Alexandre F.; Malm, Olaf; Lepoint, Gilles; Bisi, Tatiana L.; et al.
Abstract: A previous investigation of our research team has demonstrated the suitability of using hepatic total tin (ΣSn) concentrations for evaluating dolphin exposure to organotins (OTs). The present study develops the previous technique into three different approaches that comprise data: (1) on hepatic ΣSn concentrations of 121 Guiana dolphins ( Sotalia guianensis ) from five different coastal areas (CAs): (2) on ΣSn, δ 13 C and δ 15 N for 40 dolphins from Rio de Janeiro state (RJ), including ten different delphinid species; as well as (3) on hepatic ΣSn concentrations and δ 15 N values on 31 individuals from five different fish species from Sepetiba Bay (SB, Rio de Janeiro-RJ, Brazil). Hepatic ΣSn concentrations of Guiana dolphins from Guanabara Bay (GB, RJ) were significantly higher than those found in other four CAs from S and SE Brazilian regions. Significant positive correlations were found between ΣSn concentrations and δ 13 C data in delphinid species, demonstrating a coast-ocean gradient in dolphin exposure to OTs in RJ state. Significant and positive correlations were observed between ΣSn concentrations and both δ 15 N and Trophic Position (TP) values of fish, as well as high values were found for Trophic Magnification Factor (TMF = 3.03) and Trophic Magnification Slope (TMS = 0.14), demonstrating OT biomagnification in SB ichthyofauna. Highlights: OT biomagnification (via ΣSn concentrations) was found in Sepetiba Bay ichthyofauna. Decreasing coast-ocean OT concentrations were found in dolphins from Rio de Janeiro. Guanabara Bay (RJ, Brazil) is a major hotspot of environmental contamination by OTs. The TMF value for ΣSn was similar to those found in literature for TBT, DBT and ΣBT. Total tin (ΣSn) positively correlated to total length in juvenile Guiana dolphins.